2018
DOI: 10.1002/jso.25025
|View full text |Cite
|
Sign up to set email alerts
|

Does the number of sentinel lymph nodes removed affect the false negative rate for head and neck melanoma?

Abstract: In HN melanoma cases in which multiple nodes are identified, removal of all SLNs will more adequately stage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Melanoma traditionally affects males at almost twice the rate of women and most often occurs on sun‐exposed regions of the body 28 . The demographic makeup of our study is congruent with those previously reported concerning advanced age and preponderance of males 16,20,22,29 . The majority of patients included in this analysis were found to have an increased mitotic rate, T stage >T1, and Clark's level > 3.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Melanoma traditionally affects males at almost twice the rate of women and most often occurs on sun‐exposed regions of the body 28 . The demographic makeup of our study is congruent with those previously reported concerning advanced age and preponderance of males 16,20,22,29 . The majority of patients included in this analysis were found to have an increased mitotic rate, T stage >T1, and Clark's level > 3.…”
Section: Discussionsupporting
confidence: 89%
“… 28 The demographic makeup of our study is congruent with those previously reported concerning advanced age and preponderance of males. 16 , 20 , 22 , 29 The majority of patients included in this analysis were found to have an increased mitotic rate, T stage >T1, and Clark's level > 3.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, performance of sentinel lymph node biopsy (SLNB), which is useful for control of recurrence and regional disease, often is challenging in patients with HNM and often produces false-negative results. 32-37…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, approximately 13% of the patients in the MSLT‐2 trial had head and neck primary melanomas; although univariate forest plot analysis suggested a trend in favor of CLND for patients who had a head and neck primary, it was not statistically significant. Although randomized data specific to head and neck melanoma are lacking regarding prediction of occult positive nodes (ie, detected by SLN biopsy) and especially of predicting non‐SLNs, non‐randomized and population level studies have supported that subsites of the scalp, neck, and face as well as tumor thickness, ulceration, and mitoses are associated with increased rates of occult nodal positivity while non‐SLN may be more likely in head and neck patients overall, when fewer SLNs are removed, with scalp primary location, and with increasing SLN tumor burden 29‐32 . Additional randomized or multi‐institutional studies would help inform if these often‐discussed aspects of risk for non‐SLN disease in head and neck melanoma are supported by more rigorous data.…”
Section: Surgical Management: Stage I‐iiimentioning
confidence: 99%